2002
DOI: 10.1046/j.0003-2409.2001.02648.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome evaluation in a surgical intensive care unit in Barbados

Abstract: SummaryThe performance of the Acute Physiology and Chronic Health Evaluation II scoring system was prospectively assessed in the surgical intensive care unit at the Queen Elizabeth Hospital, Barbados. A total of 309 patients admitted consecutively during a 2-year period (1999)(2000)(2001) were evaluated. Demographic data, diagnosis, Acute Physiology and Chronic Health Evaluation II score, duration of stay and hospital outcome were recorded. The predicted mortality for every patient and the costs incurred were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
1
14
1
6
Order By: Relevance
“…The mean length of stay for non-survivors (9.3 days) was lower than that reported (14 days) from the previous study (3). The length of stay in the present study is lower than that predicted using APACHE IV.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The mean length of stay for non-survivors (9.3 days) was lower than that reported (14 days) from the previous study (3). The length of stay in the present study is lower than that predicted using APACHE IV.…”
Section: Discussioncontrasting
confidence: 55%
“…The original 'APACHE I' has undergone various modifications, resulting in the current APACHE IV (2). In Barbados and in the other English-speaking Caribbean countries, several studies reported the use of APACHE II to stratify ICU patients and evaluate mortality and performance (3,4). Literature search did not reveal any reports from the Caribbean region evaluating APACHE IV.…”
Section: Introductionmentioning
confidence: 99%
“… Comparison of cost blocks between Trinidad, Barbados and UK (Barbados data from [8]; UK data from [16]). …”
Section: Resultsmentioning
confidence: 99%
“…The proportion of expenditure for Clinical support services was comparable between the UK and Trinidad, whereas the Barbados study showed a very high proportion for this block (Fig. 2) [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation